Algebra of Bergman Operators with Automorphic Coefficients and Parabolic Group of Shifts - Mozel’, V. A.; Chernetskii, V. A.; Мозель, В. А.; Чернецкий, В. А.; Мозель, В. А.; Чернецкий, В. А. (Institute of Mathematics, NAS of Ukraine, 2001)
UDC 517.983